2011
DOI: 10.1002/agr.20279
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to transaction costs: evidence from banana markets in Ethiopia

Abstract: Banana producers in Ethiopia sell their produce through wholesale traders, cooperatives, and to village retailers and local consumers. Factors determining the selection of marketing channels and their implication on the agri-food industrial organization have been given little attention in the literature. This paper uses a transaction cost economics (TCE) approach to explain farmers' choice between wholesale traders and marketing cooperatives. By using a Tobit model, an effort is exerted to demonstrate the empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
11
0
10
Order By: Relevance
“…A number of studies (Arinloye et al , 2015; Mabuza et al , 2014; Ouma et al , 2010; Shiimi et al , 2012; Woldie and Nuppenau, 2011) also found that farmers marketing channel decisions were predominantly affected by different transaction cost, socio-economic, demographic and farm characteristics variables. The most common and important variables in these studies include age and education of the farmer, years of experience, farm size, transportation cost, market information search costs, bargaining power, level of payment uncertainty and distance to markets (Arinloye et al , 2015; Mabuza et al , 2014; Ouma et al , 2010; Shiimi et al , 2012; Woldie and Nuppenau, 2011). Although these different studies did not account for the similar types of variables, they can be categorised broadly under transaction cost, socio-economic, demographic and farm characteristics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A number of studies (Arinloye et al , 2015; Mabuza et al , 2014; Ouma et al , 2010; Shiimi et al , 2012; Woldie and Nuppenau, 2011) also found that farmers marketing channel decisions were predominantly affected by different transaction cost, socio-economic, demographic and farm characteristics variables. The most common and important variables in these studies include age and education of the farmer, years of experience, farm size, transportation cost, market information search costs, bargaining power, level of payment uncertainty and distance to markets (Arinloye et al , 2015; Mabuza et al , 2014; Ouma et al , 2010; Shiimi et al , 2012; Woldie and Nuppenau, 2011). Although these different studies did not account for the similar types of variables, they can be categorised broadly under transaction cost, socio-economic, demographic and farm characteristics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Searching information costs are costs incurred before the transaction. This is a common practice by farmers to gather some sort of price information and this is not free of charge (Woldie and Nuppenau, 2011). In this study, the cost is calculated by the action of searching for a market price before farmers selling their produce.…”
Section: Variables Definition and Descriptive Analysismentioning
confidence: 99%
“…Moreover, a producer's choice of a marketing outlet according to Park and Lohr (2006) is dependent on his/her utility maximization, outlet characteristics and the producers' marketing experience. In addition to farmer and farm characteristics, transaction costs form another major part of the marketing channel choices among producers (Woldie and Nuppenau, 2011).…”
Section: Conceptual Frameworkmentioning
confidence: 99%